OPTIMIZING MICROSOFT AZURE WORKLOADS leverage the well-architected framework to boost performance, scalability, and cost efficiency - Skaria, Rithin (Packt Publishing Ltd., 2023)
Master Azure Well-Architected Framework and improve your optimization skills by enhancing the quality of your workloads Purchase of the print or Kindle book includes a free PDF eBook Key Features Learn Well-Architected Framework from a cloud solution architect and an official Microsoft trainer Optimize your workloads in Azure by following Microsoft recommended best practices Use reference architecture and Microsoft tests to conduct Well-Architected Framework (WAF) assessment Book Description It's easy to learn and deploy resources in Microsoft Azure, without worrying about resource optimization. However, for production or mission critical workloads, it's crucial that you follow best practices for resource deployment to attain security, reliability, operational excellence and performance. Apart from these aspects, you need to account for cost considerations, as it's the leading reason for almost every organization's cloud transformation. In this book, you'll learn to leverage Microsoft Well-Architected Framework to optimize your workloads in Azure. This Framework is a set of recommended practices developed by Microsoft based on five aligned pillars; cost optimization, performance, reliability, operational excellence, and security. You'll explore each of these pillars and discover how to perform an assessment to determine the quality of your existing workloads. Through the book, you'll uncover different design patterns and procedures related to each of the Well-Architected Framework pillars. By the end of this book, you'll be well-equipped to collect and assess data from an Azure environment and perform the necessary upturn of your Azure workloads. What you will learn Dive deep into the Azure Well-Architected Framework Explore the differences between Cloud Adoption Framework and Well-Architected Framework Understand the pillars of the Well-Architected Framework Discover varied techniques to improve the cost profile of your workload Optimize your workflows using Azure Advisor and its score Plan and prioritize the implementation of security recommendations from WAF assessments Who this book is for This book is for developers, cloud solution architects, cloud administrators, and professionals experienced in design, implementation, and management of Azure resources. Professionals looking to learn cloud optimization or switch to a new role related to architecture can benefit from this book. An intermediate level understanding of the Microsoft Azure platform and services is a must. Experience in implementing or designing solutions in Azure is a plus but not mandatory.
Keywords: Microsoft Azure (Computing platform); Cloud computing; Microsoft Azure (Plateforme informatique); Infonuagique